The Classical Classical Fallacy - Samuelson, Paul A. (Journal of Economic Literature, 2016)
A FLAGRANT ERROR dogged James Steuart, Adam Smith, David Ricardo, John Barton, John Stuart Mill, Karl Marx, and classical writers generally. Modern commentators on classicism are enough tempted by the fallacy to generally overlook it as a vital flaw in the earlier writers. This fallay can be called classically classical-not in the sense of being the greatest error in the classical paradigm (an award that would be hard even to define) but-in the sense that modern scholars ignorant of pre-1900 literature would be little tempted by it. I do not denigrate or patronize a great writer of the past, such as David Ricardo, when I objectively delineate his hits and misses. The fallacy can be simply put. Fixed capitals are prejudicial to wages and the demand for labor; circulating capitals (wage fund items that represent outlays paid to workers at the beginning of a period of production, which are not recouped until the end of that period of production and which of course bear an interest or profit rate during the transition) are allegedly favorable to the real rate and to the demand for labor. Fixed capitals are durable produced inputs that render their services over a number of different production periods. Circulating capitals are produced inputs used up within one period of production; they are relatable to, but distinguishable from, wage fund advances paid to workers at the beginning of a period of production, to be recouped at its end along with an interest or profit return. In the minds of heterodox economists and the lay public generally, a technological change that made machinery newly viable was supposedly the kind of invention that could put people out of work temporarily, reduce market-clearing rates, and in long-run equilibrium at an unchanged subsistence rate call for a significantly reduced population. By contrast, therefore, a new invention that displaced machinery in favor of various raw materials as inputs, would supposedly raise the short-run real and increase the demand for labor. So powerful was the grip of what I shall dub the Classical Fallacy that it was being reminded of it in 1819-21 that appears to have enabled Ricardo to recant, in his famous Third Edition chapter on machinery, his previous boner that every viable invention can be expected to raise every factor's return. From today's wisdomor indeed the wisdom of 1900-that previous position of Ricardo was nonsense. There is no Invisible Hand that seeks out machines or new techniques only if they benefit everyone.I